ANALYSIS OF THE INFLUENCE OF PEDAGOGIC COMPETENCE, DIGITAL LEADERSHIP ON CAREER DEVELOPMENT - Rahmatsah Putra; Rusyidi Abubakar; Anwar Puteh; Marbawi; Ibrahim Qamarius; Yulius Dharma (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research aims to find out the influence of pedagogical competence and digital leadership on career development's impact on the performance of East Aceh State High School teachers. The data in this study used primary data in the form of questionnaires compiled following indicators of research variables and distributed to 180 teachers of East Aceh State High School with sampling techniques conducted in the first stage of stratified random sampling then carried out with simple random sampling techniques or simple randomization of respondents in this study. Data analysis methods are used by structural analysis (SEM) and processed with the analysis of structural moments (AMOS) program. The results of the study found that there is an influence of pedagogical competence and digital leadership on career development and teacher performance, there is also digital leadership influence on the performance of High School teachers in East Aceh Regency. Furthermore, the results of this study show that pedagogical competence predominantly affects the performance of East Aceh State High School teachers.